Subdiaphragmatic Lymph Nodes Uptake on 18F-FDG PET/CT After COVID-19 Vaccination in the Thigh. (March 2022) - Quak, Elske; Morel, Adeline; Faudemer, Julie; Levy, Christelle; Ciappuccini, Renaud
Abstract : Abstract: Since worldwide COVID-19 vaccination, 18 F-FDG uptake in reactive axillary lymph nodes has been frequently observed in PET/CT studies. We describe a patient with breast cancer who underwent 18 F-FDG PET/CT 7 days after receiving COVID-19 vaccination in the right thigh. 18 F-FDG uptake was observed in nonenlarged right-sided inguinal, iliac, and para-aortic lymph nodes. As the thigh can be used as an alternate site for COVID-19 vaccine injection in case of lymphedema in both arms or for adequate axillary staging in patients with breast cancer, physicians should be aware of such 18 F-FDG uptake pattern.